Heavy metal contamination in rice, pulses, and vegetables from CKDu-endemic areas in Cuttack district, India: a health risk assessment - Mohanty, Shraddha; Nayak, Rabindra Kumar; Jena, Bandita; Padhan, Kshitipati; Mohapatra, Kiran Kumar; Sahoo, Sanjib Kumar; Dash, Prava Kiran; Das, Jyotirmayee; Behera, Sujit Kumar; Sahu, Anukiran; Nayak, Jitendra Kumar; Padhan, Sudipta; et al. (Frontiers in Environmental Science, 2023)
Chronic kidney disease of unknown aetiology (CKDu) is an emerging public health concern in India. The present study was carried out to investigate the concentrations of potentially toxic heavy metals (Cd, Pb, Ni, Cr, Hg, and As) in locally grown food crops (rice, pulses, and vegetables) in CKDu prevalent areas of Cuttack district, India. Exposure risks from food crops were analysed, including estimated daily intake, hazard quotient, hazard index, and carcinogenic risk. The overall heavy metal concentrations in the crop samples were in the following order: Pb>Ni>Cd>Cr>As>Hg. The mean concentration of heavy metals in different crops were as follows, ranked from highest to lowest: spinach, rice, okra, mustard, potato, carrot, tomato, green gram, black gram. A statistical multivariate analysis revealed that the primary sources of Cd, Pb, Ni, Cr, Hg, and As in crop samples were both natural and human activities. For lead, target hazard quotient (THQ) values in rice were greater than 1, indicating significant noncarcinogenic health risks to both adults and children. While the majority of the crop samples had Pb levels below the permissible level (10 -5 ), the target carcinogenic risk of Cd was higher than the USEPA threshold value (10 -4 ), showing a cancer risk to adults and children. This study concluded that long-term intake of locally grown food crops may produce a significant health risk to the local inhabitants, and that of regular heavy metal monitoring is strongly recommended in this region.